Treatment of Chronic Prosthetic Joint Infection after Total Knee Arthroplasty with Two-stage Revision - Rizaldy, Muhammad Bayu; Santoso, Asep; Mariyanto, Ismail; Sibarani, Tangkas; Anwar, Iwan Budi (The Hip and Knee Journal, 2024)
Periprosthetic joint infection (PJI) is common among complications of knee arthroplasty. Treatment is based on many factors in each patient individually, especially the time onset of infection whether it is acute or chronic. Two stage revision is the best method in chronic PJI case under certain circumstances. There are few patients in three years period whom diagnosed with chronic PJI after Total Knee Arthroplasty (TKA). All patients diagnosed more than three months postoperatively, confirmed by clinically sinuses on the knee, and some patients have blood test and radiological sign of infection. All treated with two stage revision which is debridement, removal all implant put articulating knee spacer in the first operation, continue with arthroplasty with constrain implant in the second operation after infection confirmly eradicated and treated by one consultant surgeon in the same hospital. All patients treated with the same method have good results which are no pain, stable knee and satisfying knee Range of motion (ROM) following different recovery time. Two-stage revision have a good success rate in chronic PJI treatment as long as the patient fulfill the treatment criteria.